Evaluation and improvement of inventory management and control in a paint marketing company to reduce waste and loss of products - Cota Pardini, Yuridia Belén (2025)
Inventory is a fundamental part of the resource management of any company. There are different, each with specific characteristics and functions according to the needs and objectives of the organization. In this research, tools such as classification by ABC model, establishment of policies and FIFO procedure were applied, allowing an inventory system to be designed for a paint marketing company to have adequate control, classification and rotation of merchandise with the objective of reducing losses. economical for obsolete products. With the analysis of the diagnosis carried out, it was possible to detect more than 100 existing products that were considered obsolete, generating a significant cost for the company. In addition, it was possible to identify nearly 400 products that were poorly located within the warehouse, being able to classify them appropriately. In conclusion, the results showed a significant reduction in the inventory obsolescence rate, going from 1,31 % to 0,34 %.